Advancing Taiwan’s Semiconductor Industry: Capitalizing on its Comparative Advantage at the Global, Regional, and Firm Levels - Florencia Huang , Fu-Chuan (2024)
Taiwan's substantial growth in the 21st century is primarily driven by its production of crucial semiconductors, essential for the Fourth Industrial Revolution, technological advancements, and military enhancements. This prominence has positioned Taiwan as a vital player in the global semiconductor industry. This paper argues that Taiwan's semiconductor success is not only due to its strategic partnerships, especially with Silicon Valley, but also its comparative advantages in industrial, institutional, and firm-level aspects as part of a catch-up strategy. The study explores Taiwan’s trajectory in semiconductor development, analyzing its competitive edge through the lenses of catch-up theories, global production networks and value chains, industrial clusters, and geopolitical factors. It concludes that Taiwan's competitive edge is shaped by state-driven institutional and industrial advantages and by firms' fast-follower strategies. These advantages are embedded within the global high-tech division of labor and supported by the regional network of the Hsinchu Science and Industrial Park, which facilitates pooled human resources, technological transfer, collaborative vertical division of labor, and complementary industries. Recent geopolitical tensions have reinforced the semiconductor alliance, pushing TSMC to expand globally. While this expansion enhances collaboration, it also increases competition and challenges. Nonetheless, Taiwan's semiconductor dominance, based on these advantages, remains difficult to replicate elsewhere.